2021
DOI: 10.1111/fme.12486
|View full text |Cite
|
Sign up to set email alerts
|

Variations in migration behaviour and mortality of Atlantic salmon smolts in four different hydroelectric facilities

Abstract: Migration behaviour, route selection and mortality of Atlantic salmon, Salmo salar L., smolts were studied at four different hydroelectric facilities in the River Mustionjoki, Finland, in May 2017. Radio‐tagged smolts were released upstream of the power stations and tracked by stationary antenna‐receiver systems and hand‐held receivers. Tracking revealed a general tendency of smolts to move downstream with the main flow, but also variable behaviour and mortality related to diverse conditions characteristic of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The choice of the smolts between these two migration routes might have depended on the discharge repartition. As suggested in the literature, the downstream-migrating smolts usually tend to follow the main flow [7,11,22,27,30,42], and therefore migrate through the main river. The nature-like fishway was associated with 22-28% of the total river discharge, which corresponds to a mean discharge of approximately 4.0 m 3 s −1 .…”
Section: Discussionmentioning
confidence: 84%
“…The choice of the smolts between these two migration routes might have depended on the discharge repartition. As suggested in the literature, the downstream-migrating smolts usually tend to follow the main flow [7,11,22,27,30,42], and therefore migrate through the main river. The nature-like fishway was associated with 22-28% of the total river discharge, which corresponds to a mean discharge of approximately 4.0 m 3 s −1 .…”
Section: Discussionmentioning
confidence: 84%
“…Among the 1091 studies, some studies with data initially met our exclusion criteria but were excluded at the end. These studies included the following: (1) studies that used any form of artificial intervention, such as an enclosure (e.g., Thiem et al, 2013, 2016), attraction flows (e.g., Burnett et al, 2014; Dodd et al, 2018; Yoon et al, 2016), and strobe lights (e.g., Croze et al, 1999), to affect the approaching or ascending of fishes; (2) those that only considered downstream migration of fishes (e.g., Karppinen et al, 2021; Ovidio et al, 2021; Sanz‐Ronda et al, 2021); (3) those based on laboratories or other unnatural conditions (e.g., Baek et al, 2022; Fox et al, 2016); (4) those that reported the number of fish detected with monitoring equipment failure (e.g., Stuart et al, 2008); (5) those that did not track individual fish (e.g., Bunt, 2001; Hawkins et al, 2018; Hu et al, 2020); and (6) those that used the same monitoring data (e.g., Bao et al, 2019; Chen et al, 2018; Franklin, 2009; Franklin et al, 2012; Roscoe et al, 2010, 2011; Roscoe & Hinch, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…When ready, smolts lose their willingness to maintain station in a flow and start migrating downstream with the aid of the current. The speed of the current influences the downstream travel time, but smolts actively swim, typically following the mainstream in the surface water layer [7,120,139]. Smolts predominantly migrate at night, but this may change later in the migration period [2,5,140].…”
Section: Smolt Migrationsmentioning
confidence: 99%